تعليـم مفـردات اللغة العربية عبر برنامج الوسـائط المتعددة الفعّال - Nurkhamimi Zainuddin; Muhammad Sabri Sahrir; Mohd Shahrizal Nasir; Mohammad Najib Jaffar (Universiti Sains Islam Malaysia, 2024)
This study attempts to analyze the design principles of multimedia program for teaching Arabic vocabulary via Moodle platform. The researchers mentioned about the research tools, research samples and theories which are related to the design and development process. This study used “Needs Analysis Questionnaire” in conducting its research procedures. 100 level-one students and two lecturers from the Center for Foundation Studies, International Islamic University Malaysia had participated in the study which was carried out during the semester two of 2012/2013 academic year. The authors employ the results from this questionnaire in the development of multimedia program for teaching and learning Arabic vocabulary via Moodle and learned through the Moodle.